Heavy Metals and Biochemical Composition of Four Sea Bream Species (Acanthopagrus schlegelii Bleeker, Pagrus major Temminck & Schlegel, Oplegnathus fasciatus Krøyer and Girella punctata Gray) - Bae, Jin Han; Lim, Sun Young (2012)
To evaluate the nutritional value and safety of sea bream, the heavy metal content and biochemical composition of four sea bream species (Acanthopagrus schlegelii Bleeker, Pagrus major Temminck & Schlegel, Oplegnathus fasciatus Krøyer and Girella punctata Gray) were compared. O. fasciatus and G. punctata contained higher Hg levels compared with A. schlegelii and P. major (p<0.05). The concentrations of these heavy metals in the sea breams were lower than the mandated levels set by the Food Code of Korea. Of the four species, G. punctata had the highest moisture content (75.99%), O. fasciatus and A. schlegelii had high crude fat content (5.52%) than the other two species and P. major the highest crude protein content (22.14%). No significant differences were noted in terms of ash content. In addition, P. major, O. fasciatus and G. punctata contained fatty acids in the following order: polyunsaturated fatty acid (PUFA) > saturated fatty acid (SFA) > monounsaturated fatty acid (MUFA), whereas A. schlegelii had PUFA > MUFA > SFA levels. The main SFA was 16:0 and the main PUFAs were 20:5n-3 and 22:6n-3. A. schlegelii, P. major and G. punctata had higher percentages of glutamic acid, aspartic acid and leucine compared with O. fasciatus (p < 0.05). P. major had the best-quality fatty acid and amino acid contents, indicating that this species would likely offer the maximum nutritional benefit to humans.
Keywords: Sea bream; Heavy metals